Persepsi Mahasiswa terhadap Partai Peserta Pemilu 2014 - Rani, Syamsul (UIN Antasari Banjarmasin, 2014)
This paper discusses the students perceptions of the political parties participating in the communication process of the 2014 elections in terms of political communicator, messages, channels or media, targets , and the effects of political communication. Based on students perceptions of the five factors of political communication process it is found that a very good political communicator is from the Golkar Party, namely 28.6% of respondents, very good political message of the Democratic Party 31.0%, or excellent media channel of political party of NasDem 26.2%, the excellent political targets of NasDem Party 19.0%, and the very good effects of political communication from Hanura 16.7%. This article suggests the need for improving socialization of political parties including the five factors of political communication process, so that the party eletability level will be better and the level of community abstentions can be pressed or lowerer